Recent progress in magnetic applications for micro- and nanorobots - Xu, Ke; Xu, Shuang; Wei, Fanan (Beilstein Journal of Nanotechnology, 2021)
In recent years, magnetic micro- and nanorobots have been developed and extensively used in many fields. Actuated by magnetic fields, micro- and nanorobots can achieve controllable motion, targeted transportation of cargo, and energy transmission. The proper use of magnetic fields is essential for the further research and development of micro- and nanorobotics. In this article, recent progress in magnetic applications in the field of micro- and nanorobots is reviewed. First, the achievements of manufacturing micro- and nanorobots by incorporating different magnetic nanoparticles, such as diamagnetic, paramagnetic, and ferromagnetic materials, are discussed in detail, highlighting the importance of a rational use of magnetic materials. Then the innovative breakthroughs of using different magnetoelectric devices and magnetic drive structures to improve the micro- and nanorobots are reviewed. Finally, based on the biofriendliness and the precise and stable performance of magnetic micro- and nanorobots in microbial environments, some future challenges are outlined, and the prospects of magnetic applications for micro- and nanorobots are presented.
Keywords: magnetic drives; magnetic nanoparticles; magnetoelectric devices; micro- and nanorobots